Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Setting-specific Transmission Rates: A Systematic Review and Meta-analysis. (9th February 2021) - Thompson, Hayley A; Mousa, Andria; Dighe, Amy; Fu, Han; Arnedo-Pena, Alberto; Barrett, Peter; Bellido-Blasco, Juan; Bi, Qifang; Caputi, Antonio; Chaw, Liling; De Maria, Luigi; Hoffmann, Matthias; et al.
Abstract: Background: Understanding the drivers of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission is crucial for control policies, but evidence of transmission rates in different settings remains limited. Methods: We conducted a systematic review to estimate secondary attack rates (SARs) and observed reproduction numbers (Robs ) in different settings exploring differences by age, symptom status, and duration of exposure. To account for additional study heterogeneity, we employed a beta-binomial model to pool SARs across studies and a negative-binomial model to estimate Robs . Results: Households showed the highest transmission rates, with a pooled SAR of 21.1% (95% confidence interval [CI]:17.4–24.8). SARs were significantly higher where the duration of household exposure exceeded 5 days compared with exposure of ≤5 days. SARs related to contacts at social events with family and friends were higher than those for low-risk casual contacts (5.9% vs 1.2%). Estimates of SARs and Robs for asymptomatic index cases were approximately one-seventh, and for presymptomatic two-thirds of those for symptomatic index cases. We found some evidence for reduced transmission potential both from and to individuals younger than 20 years of age in the household context, which is more limited when examining all settings. Conclusions: Our results suggest that exposure in settings with familiar contacts increases SARS-CoV-2 transmission potential. Additionally, the differences observed in transmissibility by index case symptom status and duration of exposure have important implications for control strategies, such as contact tracing, testing, and rapid isolation of cases. There were limited data to explore transmission patterns in workplaces, schools, and care homes, highlighting the need for further research in such settings. Abstract : In this review, we systematically explore factors that affect transmission of SARS-CoV-2, such as age, symptom status, setting, and duration of contact. Our results highlight the importance of targeting interventions in settings where close and prolonged contacts occur.